Influence of feeding system on fatty acid composition of suckling lambs - Caparra P.; Foti F.; Scerra M.; Cilione C.; Vottari G.; Galofaro V.; Sinatra M.C.; Scerra V. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
The main objective of the present work was to determine ewe dietary treatment effects on intramuscular fatty acid composition of suckling lambs. Twenty-four pregnant Merinizzata Italiana ewes were divided into two groups of twelve each. One group was allowed to graze (grass group) and the other group was penned indoors and was fed hay ad libitum and commercial concentrate (stall group). After lambing, all ewes stayed with their respective lambs for the duration of the trial. The lambs were slaughtered at 100 days of age. Milk and lamb meat (longissimus dorsi muscle) fatty acids were analysed. The intramuscular fat of the grass group showed higher (P<0.001) proportions of polyunsaturated fatty acids (PUFA) than the stall group. The percentage of C12:0, C16:0 and C18:1 cis-9 were higher (P<0.05, P<0.001 and P<0.001) in the intramuscular fat of the stall group, whereas the grass group showed greater proportion of C18:3 (P<0.001). Moreover, eicosapentaenoic acid (C20:5 n-3) and docosapentaenoic acid (C22:5 n-3) were found in the highest amounts (P<0.001, P<0.01) in the meat of the grass group. PUFA/SFA ratio was higher (P<0.001) in the intramuscular fat of the grass group and n-6/n-3 ratio was lower (P<0.001) than the stall group. In contrast with previous work, this study has not found a significant difference in the proportion of C18:2 cis-9, trans-11 in the intramuscular fat within the two groups. This could be attributed to the poor condition of the pasture in the final phase of the trial and, mainly, to the young age of the lambs. This study confirmed that pasture enhanced the unsaturated fatty acid profile of intramuscular fat in lambs including omega-3 fatty acids.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)